2010
DOI: 10.1172/jci39721
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of C/EBPβ alleviates ER stress and pancreatic β cell failure through the GRP78 chaperone in mice

Abstract: Pancreatic β cell failure is thought to underlie the progression from glucose intolerance to overt diabetes, and ER stress is implicated in such β cell dysfunction. We have now shown that the transcription factor CCAAT/ enhancer-binding protein β (C/EBPβ) accumulated in the islets of diabetic animal models as a result of ER stress before the onset of hyperglycemia. Transgenic overexpression of C/EBPβ specifically in β cells of mice reduced β cell mass and lowered plasma insulin levels, resulting in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
95
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 39 publications
10
95
1
Order By: Relevance
“…We first studied leptin-receptor-deficient db/db mice on the C57BLKS genetic background. These mice are a well-established β cell ER stress model, due to a combination of elevated insulin demand from insulin resistance and the C57BLKS genetic influence, which is predisposed to β cell ER stress and failure (29)(30)(31)(32). At 4 weeks of age, db/db mice still had near-normal body weight and blood glucose, but they showed UPR activation as determined by BiP immunostaining ( Figure 5, A-D).…”
Section: Proteomics Screen To Identify In Vivo Drivers Of β Cell Prolmentioning
confidence: 99%
See 1 more Smart Citation
“…We first studied leptin-receptor-deficient db/db mice on the C57BLKS genetic background. These mice are a well-established β cell ER stress model, due to a combination of elevated insulin demand from insulin resistance and the C57BLKS genetic influence, which is predisposed to β cell ER stress and failure (29)(30)(31)(32). At 4 weeks of age, db/db mice still had near-normal body weight and blood glucose, but they showed UPR activation as determined by BiP immunostaining ( Figure 5, A-D).…”
Section: Proteomics Screen To Identify In Vivo Drivers Of β Cell Prolmentioning
confidence: 99%
“…To determine whether ER stress applied directly to the β cell increases β cell proliferation in vivo, we studied heterozygous Ins2 C96Y/+ (herein referred to as Akita) mice, in which a mutant proinsulin (1 of 4 insulin alleles) causes β cell ER stress due to improper disulfide formation (32,33). These mice are born with normal glucose tolerance but become diabetic by adulthood due to ER stress-induced β cell failure (34,35).…”
Section: Proteomics Screen To Identify In Vivo Drivers Of β Cell Prolmentioning
confidence: 99%
“…For example, the overexpression of the ER chaperone BiP in b-cells protects mice against HFD-induced diabetes (39). Conversely a reduction in BiP expression as a result of C/EBPb-mediated downregulation of ATF6 is associated with diabetes (43). Moreover, administration of pharmacological chaperones such as tauroursodeoxycholic acid, 4-phenylbutyrate (PBA), and the more recently discovered azoramide can restore rodent islet function both in vitro and in vivo (32,36,40,(44)(45)(46).…”
Section: B-cell Compensation: a Positive Role For The Uprmentioning
confidence: 99%
“…It has been suggested that the UPR plays a protective role in the adaptation of the β-cell to increased insulin production (12,13). UPR pathways mediated by IRE1/XBP1 and ATF6 have been implicated in insulin secretion and β-cell survival, but their in vivo functions in β-cells are not fully understood (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%